Research Trends in the Application of Problem Based Learning Model in chemistry learning in Indonesia: A Systematic Literature Review - Muhammad Habib Ash Shiddiqi; Purwaningsih , Dyah; Pujiana, Elma (IJCER (International Journal of Chemistry Education Research), 2025)
This study aims to analyze and map research trends on the application of the Problem-Based Learning (PBL) model in chemistry education in Indonesia using the systematic literature review (SLR) method. The study involved secondary data sourced from the SINTA database for publications between 2015 and 2024. Articles were identified using the keywords "problem-based learning" and "chemistry", with inclusion criteria comprising: (1) studies implementing PBL in chemistry learning, (2) published between 2015 and 2024, (3) document type limited to peer-reviewed articles, and (4) articles indexed at least by Sinta 3. Out of an initial 182 articles retrieved, only 21 articles met the inclusion criteria after screening. The results indicate the PBL model has been implemented using various approaches, strategies, and media, demonstrating its effectiveness in improving students' learning outcomes, critical thinking skills, and engagement in chemistry education. The most frequent research focus was on learning outcomes, followed by learning activities and critical thinking skills, while other variables such as scientific attitudes, self-efficacy, and collaboration also received attention. PBL's adaptability, including integration with STEM and digital media, enhances its relevance to modern learning demands. This study highlights the significant role of PBL in fostering student-centered learning and bridging theoretical and practical aspects of chemistry. Limitations in database scope and inclusion criteria highlight the need for broader reviews. Future studies should include meta-analyses and explore interdisciplinary applications to enhance PBL's potential in chemistry education. These findings offer valuable insights for educators and researchers aiming to optimize PBL in Indonesian education